Minas a céu aberto de Moçambique - Munguambe, Arcénio Artur; Mandlate, Clarência Matias (Wutivi University, 2018)
Moçambique é um dos países da África com muitos recursos naturais. O grau de conhecime nto geológico até agora atingido, mostra que todos os recursos minerais considerados apresentam perspectivas favoráveis para a sua exploração. A indústria extrativa é o sector que tem grandes empregadores de mão-de-obra e tem um grande impacto rural podendo constituir grandes focos de desenvolvimento e de combate a pobreza nas áreas onde se encontra inserido. Neste caso, o presente trabalho visa identificar os principais recursos naturais e agrupar em metálicos e não metálicos e as respectivas empresas mineradoras.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais